Uso racional y eficiencia energética en los sistema de iluminación en la Corporación Universitaria de la Costa CUC (2010)
The corporation Coast University, CUC, is no stranger to the importance that today represents the rational and efficient use of energy and reduce Co2 gas emissions to the environment in our environment. In its effort to provide a grain of sand the institution through a research group conducted a characterization lighting energy allowing it to be more efficient in the rational use with electrical power and thus get benefits such as saving energy, money and protecting the environment. This research was conducted in the years 2008, 2009 and 2010 as for the characterization is necessary to know energy consumption data, billing each year. The data obtained by the characterization made us to conclude that the CORPORATION UNIVERSITY OF COSTA CUC is not being efficient and therefore conclusions and recommendations are made to reach the next stage which would be the management system to implement.